Rectal pyogenic granulomas: an uncommon cause of gastrointestinal bleeding - Tuba Devrim; Özlem Gül Utku; Dilek Oğuz (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Devrim T, Utku ÖG, Oğuz D. Rectal pyogenic granulomas: an uncommon cause of gastrointestinal bleeding. Turk J Gastroenterol 2018; 29: 122-3.